A Conceptual Study: Marketing and Artificial Intelligence - Zineb JOUHARI; Younes LAFRAXO; Mohamed Larbi SIDMOU (Communications of International Proceedings, 2020)
Marketing is one of the areas most affected by Artificial Intelligence (AI), Building from extant research and recent developments related to the field of Artificial Intelligence, the authors offer specific answers that can lead to a better understanding especially since AI is not as easy to understand as it seems and that a good number of marketers think that AI would be beneficial to them in their work. However, the fear is felt about what it will generate once installed. We demonstrate based on Artificial intelligence replacement theory that in marketing the type of human work and the tasks play an essential role.
Keywords: Artificial Intelligence; Marketing; AI Replacement Theory.